Pengaruh Infrastruktur Transportasi terhadap Pertumbuhan Ekonomi di Kota Semarang - Haris Wahyu Kurniawan; Jaka Aminata (Universitas Diponegoro, 2023)
The availability of adequate infrastructure is a substantial factor in promoting economic growth. One important type of infrastructure is transportation. This research aims to analyze the effect of land, sea, and air transport on Indonesia’s economic growth over the period 2001-2021. This research used the Ordinary Least Square (OLS) regression method with the Panel Data-Fixed Effect Least Square Dummy Variable (LSDV) Model approach. The data structure used in this research covers the area of Semarang City. The results show that transportation land, sea, air, and gross regional domestic product (GRDP) have a positive and significant effect on Indonesia’s economic growth. The research results support the infrastructure-led growth paradigm. Furthermore, the estimation results also indicate the importance of government budget support in providing adequate infrastructure. A good infrastructure will eventually provide positive spillovers to other economic activities.